Agrobacterium mediated in planta transformation in castor (Ricinus communis L.): AGROBACTERIUM MEDIATED IN PLANTA TRANSFORMATION IN CASTOR (RICINUS COMMUNIS L.) - G LAKSHMIDEVI; K B DURGA BHAVANI; ROHINI SREEVATHSA; V DINESH KUMAR (Journal of Oilseeds Research, 2018)
Castor has been a recalcitrant crop for in vitro manipulations. To realize the potential of genetic engineering, it is essential to develop a repeatable transformation protocol. In planta transformation has been identified as a method of choice to obtain transgenic lines in crops that are trajectory to in vitro procedures. In the present investigation, we have developed an optimized protocol for realizing transgenic castor plantsthrough Agrobacterium mediated in planta transformation. We have established procedures to ensure better survival of Agrobacterium treated seedlings (T0) in transgenic green house as well as for screening T1 progeny plants to identify putative transgenic plants. The optimized factors included : growing the Agro-treated (pricked) seedlings for two days in soilrite and then transferring to soil, treating the two day old seedlings of T1 progeny plants in hygromycin solution @40mg/l for two hours and then transferring the normal looking plants to the soil in transgenic green house. Using the optimized protocol, we have realized 30 transgenic castor plants carrying different gene constructs.